Customer Culture: How FedEx® and Other Great Companies Put the Customer First Every Day - Basch, Michael (Financial Times Prentice Hall books., 2002)
Everyone talks about creating a "customer-centered culture." In CustomerCulture: How FedEx and Other Great Companies Put Their Customer First Every Day , the executive who pioneered FedExÕs legendary customer culture shows exactly how to go beyond talk and make it happen Ñ for real! Drawing on lessons learned at FedEx, Michael Basch identifies key cultural obstacles and leadership failures that dilute customer focus, and demonstrates exactly how to build systems and structures that help good people deliver outstanding service.